Effect of Organic Fertilizers on Some Agronomic andChemical Properties of Potato (Solanum tuberosum L.) - Ceylan, Safak; Mordogan, Nilgun; Akdemir, Huseyin; Cakici, Hakan (Asian Journal of Chemistry, 2010)
In the present study, we report the effects of cattle and chicken manure applied in different doses on the yield, some quality components and nutrition contents of potato. The cattle and chicken manure were applied of two different doses (0–3–6 t da–1 and 0–2–4 t da–1 respectively). The experimental soil is slightly acidic, sandy loam in texture and poor in humus, nitrogen and calcium content. The C/N ratios of the tested cattle and chicken manure were 16.3 and 15.1 respectively. In this research, the highest yield and yield component (number of tuber, weight of tuber) were obtained with application of 6 t da–1 cattle manure and 2 t da–1 chicken manure. The application of cattle and chicken manure increased tuber yields by 21% and 22% respectively compared with control. Starch content in potatoes was high with cattle manure application than chicken manure. Organic fertilizer did not significantly affect ascorbic acid content in potatoes. Maximum N, K, Ca content of leaves and N, Ca content of tubers was determined at 2 t da–1 chicken manure and 6 t da–1 cattle manure doses.